The effects of the TTIP on EU countries: An ex-ante evaluation - Jose Villaverde; Adolfo Maza (Revista de Economía Mundial, 2016)
The EU and the US are involved currently in discussions of what is called the Transatlantic Trade and Investment Partnership (TTIP). Up to now, there have been several attempts to assess the economic impact of the TTIP, both at the EU-wide level and for some of the EU countries. None of these studies, however, pays any attention to the potential impact of the TTIP on every EU country, which is the main aim of this paper. In a nutshell, the main findings indicate that the effects of the TTIP agreement are going to be small, albeit positive, and not equally distributed. More specifically, the most developed countries tend to be those that, potentially, will undergo a higher increase in their trade with the US, so they are more likely to reap benefits from the TTIP than the less developed countries. This being so, the TTIP will (weakly) increase cross-country disparities.